2014
DOI: 10.1016/j.jfda.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Application of ion mobility spectrometry for the determination of tramadol in biological samples

Abstract: In this study, a simple and rapid ion mobility spectrometry (IMS) method has been described for the determination of tramadol. The operating instrumental parameters that could influence IMS were investigated and optimized (temperature; injection: 220 and IMS cell: 190°C, flow rate; carrier: 300 and drift: 600 mL/minute, voltage; corona: 2300 and drift: 7000 V, pulse width: 100 μs). Under optimum conditions, the calibration curves were linear within two orders of magnitude with R ≥ 0.998 for the determination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Basically, IM-MS enhances signal in tandem mass spectrometry (MS-MS). This additional component in the experimental setup for proteoform identification also enhances the detection of isomers and PTMs in the investigated sample [38][39][40][41].…”
Section: Enhancement Of Ms/ms In Top/middle-down Methodsmentioning
confidence: 99%
“…Basically, IM-MS enhances signal in tandem mass spectrometry (MS-MS). This additional component in the experimental setup for proteoform identification also enhances the detection of isomers and PTMs in the investigated sample [38][39][40][41].…”
Section: Enhancement Of Ms/ms In Top/middle-down Methodsmentioning
confidence: 99%
“…Literature review: Several methods were reported for determination of TMD alone in dosage forms and different biological fluids. HPLC [40,41], GC [42], Spectrometry [43,44], and even by electrochemical methods [45,46] were reported. Simultaneous determination of TMD with other analgesics was reported using LC [47][48][49].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…In addition, HS-IMS presents a greater portability, since it works at atmospheric pressure. This technique has been successfully used for the discrimination of samples in many fields including the detection of adulterated food [ 27 , 28 ], explosives [ 29 , 30 ], drugs or pharmaceuticals substances [ 31 , 32 , 33 ] as well as for the characterization of ILs in fire debris [ 26 ]. However, how biological degradation may affect the correct identification of ILs when this technique is used is still to be studied.…”
Section: Introductionmentioning
confidence: 99%